2013
DOI: 10.1210/jc.2013-2182
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Proinsulin and Insulin in the Diagnosis of Insulinoma: A Critical Evaluation of the Endocrine Society Clinical Practice Guideline

Abstract: Using a current insulin assay 9% of insulinoma cases end the supervised fast with an insulin concentration below 5 μIU/mL. Inadequate insulin suppression defined using a threshold of ≥ 3 μIU/mL increases the sensitivity of the test. The value of the proinsulin test lies in its unique ability to distinguish cases from controls. A proinsulin concentration of ≥22 pmol/L best discriminates cases from controls. Reliance on an end of fast proinsulin cutoff value of 5 pmol/L does not augment sensitivity but greatly r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 14 publications
1
21
0
5
Order By: Relevance
“…Post-prandial hypoglycaemia is more commonly associated with nesidioblastosis, but a very small proportion (6%) of insulinomas may also present with symptoms solely occurring several hours after eating (Placzkowski et al 2009). Diagnosis of insulinoma is confirmed by inappropriately elevated insulin, C-peptide and pro-insulin levels at the time of hypoglycaemia, with resolution of symptoms after glucose administration, satisfying the diagnostic criteria known as the Whipple triad (Whipple & Frantz 1935, Cryer et al 2009, Guettier et al 2013. These blood samples may be taken opportunistically at the time of symptoms, or induced by prolonged supervised fasting or mixed-meal stimulation testing.…”
Section: Insulinomamentioning
confidence: 99%
“…Post-prandial hypoglycaemia is more commonly associated with nesidioblastosis, but a very small proportion (6%) of insulinomas may also present with symptoms solely occurring several hours after eating (Placzkowski et al 2009). Diagnosis of insulinoma is confirmed by inappropriately elevated insulin, C-peptide and pro-insulin levels at the time of hypoglycaemia, with resolution of symptoms after glucose administration, satisfying the diagnostic criteria known as the Whipple triad (Whipple & Frantz 1935, Cryer et al 2009, Guettier et al 2013. These blood samples may be taken opportunistically at the time of symptoms, or induced by prolonged supervised fasting or mixed-meal stimulation testing.…”
Section: Insulinomamentioning
confidence: 99%
“…A recent study showed that 10% of patients aged under 20 years with MEN1 developed insulinoma (Goudet et al 2015). The gold standard for the diagnosis of insulinoma is a 48-h supervised fast with negative levels of betahydroxybutyrate and sulfonylurea with a threshold for proinsulin of ≥22 pmol/L (Guettier et al 2013). Because of their small size (82% <2 cm, 47% <1 cm), insulinomas are difficult to localize and are scattered throughout the pancreas gland (Service et al 1991).…”
Section: Other Functional Duodeno-pancreatic Netsmentioning
confidence: 99%
“…The diagnosis is confirmed by the demonstration of inappropriately elevated insulin and proinsulin levels associated with serum glucose values of less than 50 mg/dL during 48 hour fast period. 3,4 Insulinoma may be associated with a hereditary syndrome in nearly 10% of patients, the most common being multiple endocrine neoplasia type 1 (MEN1) 5 . Insulinomas are evenly distributed throughout the pancreas and are usually less than 2 cm in size in approximately 90% of cases 1 .…”
Section: Introductionmentioning
confidence: 99%